Accessibility to, Acceptability of, and Adherence to HIV/AIDS Prevention Services by Men Who Have Sex with Men: Challenges Encountered at Facility Level - P. C. N. Otambo; A. Makokha; M. Karama; M. Mwangi (Advances in Public Health)
The prevalence of HIV/AIDS among men who have sex with men (MSM) in Nairobi has been reported to be 16.4% which is a public health concern. The aim of this study was to determine factors that affected accessibility to, acceptability of, and adherence to HIV/AIDS prevention services by men who have sex with men in Nairobi County, Kenya. Methods. The study used a mixed methods design, applying both quantitative and qualitative methods. Results. Over 70% of MSM reported that TB drugs, antiretroviral drugs, lubricants, condoms, and other STI treatment services were accessible. However, 31.6% of MSM reported that discrimination at the health facility level was a hindrance to accessing HIV/AIDS prevention services while 26.3% reported encountering stigma. 48.4% of MSM consumed alcohol while taking of drugs was reported, at 36.1%. Conclusion. Discrimination and stigma adversely affected MSM seeking HIV/AIDS prevention services in health facilities. MSM engaged in alcohol and substance abuse that likely affected their health seeking behavior. Although most prevention services are reported as accessible, uptake of the same needs to be considered.